Soil phosphorus cycling microbial functional genes of monoculture and mixed plantations of native tree species in subtropical China - Qin, Lin; Xiao, Zhirou; Ming, Angang; Teng, Jinqian; Zhu, Hao; Qin, Jiaqi; Liang, Zeli (Frontiers in Microbiology, 2024)
Background: Transforming coniferous plantation into broadleaved or mixed broadleaved-coniferous plantations is the tendency of forest management strategies in subtropical China. However, the effects of this conversion on soil phosphorus (P) cycling microbial functional genes are still unknown.Methods: Soil samples were collected from 0-20, 20-40, and 40-60 cm (topsoil, middle layer, and subsoil, respectively) under coniferous Pinus massoniana (PM), broadleaved Erythrophleum fordii (EF), and their mixed (PM/EF) plantation in subtropical China. Used metagenomic sequencing to examine the alterations of relative abundances and molecular ecological network structure of soil Pcycling functional genes after the conversion of plantations.The composition of P-cycling genes in the topsoil of PM stand was significantly different from that of PM/EF and EF stands (P<0.05), and total phosphorus (TP) was the main factor causing this difference. After transforming PM plantation into EF plantation, the relative abundances of P solubilization and mineralization genes significantly increased in the topsoil and middle layer with the decrease of soil TP content. The abundances of P-starvation response regulation genes also significantly increased in the subsoil (P<0.05), which may have been influenced by soil organic carbon (SOC). The dominant genes in all soil layers under three plantations were phoR, glpP, gcd, ppk, and ppx. Transforming PM into EF plantation apparently increased gcd abundance in the topsoil (P<0.05), with TP and NO3 --N being the main influencing factors. After transforming PM into PM/EF plantations, the molecular ecological network structure of P-cycling genes was more complex; moreover, the key genes in the network were modified with the transformation of PM plantation.Transforming PM into EF plantation mainly improved the phosphate solubilizing potential of microorganisms at topsoil, while transforming PM into PM/EF plantation may have enhanced structural stability of microbial P-cycling genes react to environmental changes.